Enhancing Financial Literacy to Achieve Economic Independence: Meningkatkan Financial Literacy Untuk Mewujudkan Kemandirian Ekonomi - Sofilda, Eleonora; Hariyanti, Dini; Wahyuni, Lidia (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the Indonesian economy, contributing significantly to GDP and employment absorption. Despite strong government support, many MSMEs still face major challenges, particularly in terms of low financial literacy, which hampers their ability to manage their businesses effectively. This Community Service Program (PkM) aims to enhance the financial literacy and managerial skills of Rufata MSMEs, located in Gudang Sarinah Pancoran, South Jakarta, through training tailored to their specific needs. The methods used in this PkM include needs identification, training program planning, interactive training implementation, and evaluation of the training’s effectiveness. The training was designed to improve the managerial and financial management capabilities of Rufata MSMEs, focusing on cash management, financial recording, and business decision-making. The program was attended by 20 participants and conducted in sessions that combined theory with practice, including case studies and simulations. The results of this PkM activity showed a significant improvement in the participants' understanding and skills in managing their business finances. Evaluation results through pre-test and post-test indicated an increase in scores from 40%-60% to 85%-100% after the training. Additionally, continued support such as consultations and mentoring helped participants face challenges after the training, improving the productivity and operational efficiency of Rufata MSMEs. Overall, this comprehensive approach to training proved effective in enhancing the performance of Rufata MSMEs and is expected to contribute more significantly to the national economy.